Answer:
w + 6 ≥ 27
Step-by-step explanation:
A number w is the variable w.
Increased by 6 means being added by 6.
Allison's Plant: 2.5 inches in 5 days
Yuki's Plant: 5.5 centimeters in 4 days
(HINT: How can we change the rates to compare the growth rate of the seedlings)
Your answer:
Answer:
yukis plant
Step-by-step explanation:
Answer:
I feel like you are mistaken on the first question...
6 plus 27 equals 33.
33 equals 100 percent.
What is 6 over 33? 0,18.
What's 27 over 33? 0,82.
Therefore, 19 plus 12 equals 31.
19 divided by 31 equals 0,61.
12 over 31 equals 0,39.
how you know
Answer:
Emma can play for more than one minute.
Step-by-step explanation:
1/4 is the same as 2/8 because 1/4*2=2/8.
2/8 is much smaller than 7/8.
Emma can play for 3 1/2 minutes in total.
Zeros of the given function f(x) = (x-1)(x-7) is (1, 0) and (7, 0).
Given function f(x) = (x - 1)(x - 7). Zeros of the function to be determined?
Functions are the relationship between sets of values. e g y=f(x), for every value of x there is its exists in a set of y. x is the independent variable while Y is the dependent variable.
f(x) = (x - 1)(x - 7)
for finding zero we must equal the function to zero.
f(x) = 0
(x - 1)(x - 7) = 0
Here equal to zero implies one of the parenthesis must be zero,
x - 1 = 0 or x - 7 =
x = 1 or x = 7
It shows x must be 1 or 7 so the function gives zero, i.e. coordinates (1, 0) and (7, 0) are zeros of the function f(x) = (x - 1)(x - 7).
Thus, zeros of the given function f(x) = (x-1)(x-7) is (1, 0) and (7, 0).
Learn more about function here:
#SPJ5
Answer:
(1,0) (7,0) so it’s 1 and 7
Step-by-step explanation:
You need to find the values of x that make the output equal to zero.
In a function like this, simple take the inverse of the number in each parentheses. For example if the number is -5, the zero is 5. And if it’s 5, the zero is -5.
This only works if the coefficient of x is 1.
Please mark as brainliest if you’re satisfied :)
Answer:
Step-by-step explanation:
The question is incomplete as the method is not given.
However, the question can still be solved.
Given
Make xi the subject in the first equation
Substitute 1 + x2 for xi in the second equation
Open bracket
Collect Like Terms
Solve for x2
Recall that:
The solution to the given system of equations is obtained through substitution. The process involves replacing a variable in one equation with an expression from the other. The final solutions are x1=1 and x2=0.
The system of equations in question is:
1) x1 - x2 = 1
2) 3x1 + x2 = 3
The method to solve this system is through substitution or elimination. First, rewrite the first equation x1 = x2 + 1. This allows us to substitute x1 - 1 for x2 in the second equation, yielding 3(x2 + 1) + x2 = 3, simplifying to 4x2 + 3 = 3. Solving for x2, we get x2 = 0. Substituting x2 into x1 = x2 + 1, we conclude that x1 = 1. Thus, the solution to the system is x1 = 1, x2 = 0.
#SPJ3